Impacto del dragado de sedimentos del puerto de Salaverry en el ecosistema marino litoral - Bocanegra García, Carlos A. (2018)
The impact of dredging of sediments in the port of Salaverry, main center of transport of agriculture products, minerals, petroleum and others was evaluated. The last dredging carried out in august of 2014, removed 1 163, 000 m3 of the marine bottom sediments, with a hidraulic dredge which, were sucked out and lay aside wear the port área, at the left  the right of fishermen platform.  Main chemical contaminants were determined (Pb,Zn,Cd,Cu) indicatives of the port activity . Investigations was carried out in both zones, where samples of the sediments and superficial wáter, birds and fishes were taken. The values of heavy metals were higher than the maximum permited limit according the international standars, performing negative effects on the coastal marine ecosystems making a risk to the public healt.